Analisis Pengembangan Sumber Daya Manusia Pada PT. Perusahaan Listrik Negara (Persero) UPT Kota Bengkulu - Wulandari, Wiwik; Rosidin, Rosidin (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
Human resource development is applied by every company and government agency as a form of effort from the company to measure the level of ability and expertise possessed by its resources so that its resources have a good level of quality and performance. The purpose of this research is to find out how the application of human resource development so that it will produce high-quality employees, as well as the inhibiting factors. This research uses qualitative research methods. By collecting 4 informants as sources. This research data collection technique is based on data reduction, data presentation, and data conclusions collected based on observations, interviews, and documentation conducted in the field. Based on the results of the study that human resource development as measured by motivation, education and training, career needs, fair treatment in a career, promotion, motivation, and mutation has a big role in improving the quality of human resources owned by the company. The inhibiting factor is that there are still many employees who are lazy to carry out training and unwanted job placements because they are not in accordance with their abilities. While the supporting factors are that the company has provided a special institution that is used to accommodate problems that occur, both external and internal problems, such as the education and training unit (UDIKLAT), P2K3 meetings, management derivative meetings (RTM), quarterly meetings, LKS Bipartik, and tripartite.